التحوير الفني وصراع الزمن في مسرحية "أهل الكهف" لتوفيق الحكيم - زعيمي, جميلة; محدادي, علي (جامعة الوادي - University of Eloued, 2020)
الملخص: الملخص: تحاول هذه الدراسة الوقوف على قضية الإنسان وعلاقته بالزمان حين يفقد التوازن الكافي بين الذات والحياة التي يعيشها فينتج خلل يقلب حياته رأسا على عقب، ويصل إلى قناعة مفادها أن بقاءه ووجوده لا جدوى منه، ولا يمكنه العيش لأنه فقد الصلة بما يربطه من أحلام وأهداف، ومسرحية "أهل الكهف" لتوفيق الحكيم تطرح في الأساس هذه القضية، وهذا ما تجسد في شخصياتها. والحكيم من خلال توظيفه للتراث الديني والقصة القرآنية بالتحديد أعطى للموضوع بعدا جديدا وحوره تحويرا فنيا بما يخدم أفكاره التي يريد إيصالها، وسنحاول إعطاء قراءة حول المسرحية وإبراز جانب صراع شخصياتها مع الزمن وإظهار الخلفية الحقيقة التي تجسد فكرة المسرحية والتي كانت محور نجاح بنائها الفني. والإشكالية التي يمكن أن نقف لنطرحها هي: كيف جسد الحكيم قضية الزمن في هذه المسرحية؟ وكيف تعاملت شخصيات المسرحية مع الزمن؟. Abstract: The present study looks into identifying the issue of man and in relation to time whereina disequilibrium between the self and the life is brought to the fore, producing a destabilizing effect that renders life or existence useless and unliveable owing to dreams loss .Hence, through characterization ,Tawfiq al-Hakim’s play “People of the Cave” discusses the issue. Through employing of the religious heritage: the Qur'anic storytellingin specificfurnishes the subject with a new dimension, modulating it artistically in such a way that serves ideas communication. Thus, we have attempted to suggest a general reading of the play; to highlight the conflict between its characters; and to expose a philosophical mental idea that was the centrepiece of the success of its artistic construction. The problem we can stand up for is: How did the wise man embody the cause of time in this play? And how did the characters of the play deal with the times?
مقال
Keywords: المسرح ; التراث ; أهل الكهف ; توفيق الحكيم ; الزمن; Theatre ; Heritage ; the cave people's ; Tawfiq al Hakim ; conflict of time